Metabolismo (lipídios e proteínas) e histopatologia do cérebro de ratos recém nascidos, jovens e adultos, submetidos a desnutrição proteico calórica, tipo marasmo - Kfouri, J. R. N. [UNESP]; Trindade, Cleide Enoir Petean [UNESP]; Nóbrega, Fernando José de [UNESP] (My University, 1977)
Brains of Wistar male rats (newborns, youngs and adults) submitted to protein-calorie deprivation for different periods (27, 33 and 60 days) were studied histologically and biochemically (protein and lipids contents). Lower levels of lipid, particularly among young rats, were observed in all groups. The protein levels were also significantly lower in the newborns, only slightly diminished in the youngs and not altered in the adults. On the other hand the histological study made in all groups did not show any qualitative modifications. The authors concluded that the protein-calorie deprivation affects the brain composition markedly in the earlier periods of life when the developing rate is greater. This could result in irreversible brain damage.
Lipid and protein metabolism and histopathology in brains of newborn, young and adult rats subjected to protein calorie malnutrition (marasmic type)
Keywords: brain; lipid metabolism; marasmus; protein metabolism; rat; theoretical study